PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. CAHAYA MANUNGGAL KOTA TANGERANG - Rob Sosiatri; Muhamad Subhi Badrani (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
This study aims to determine how the effect of compensation on employee performance at PT. Cahaya Manunggal – South Tangerang. The research method used in this study is associative, which is a research method based on positive philosophy and is used to examine a particular population or sample. Associative research has a higher level when compared to descriptive. With this associative research, a theory can be built that serves to explain, predict and control a symptom. The analytical method used in this research is simple regression analysis, correlation coefficient analysis, determination coefficient analysis, and partial test (t). Statistically it is proven that the value of the compensation determinant on performance is 60.4%. That is, compensation has a very large opportunity in influencing employee performance. In a broader sense, it can be understood that employee performance is highly dependent on the reward system, the better the salary and incentives offered, the greater the possibility of increasing work productivity, so that organizational goals are achieved.